2023
DOI: 10.1111/jan.15925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of burnout and work engagement in the relationship between self‐efficacy and safety behaviours—A chained mediation modelling analysis

Man Liu,
Lu Liu,
Zhuoheng Lv
et al.

Abstract: AimsTo explore the current situation, influencing factors and pathways of safety behaviour of nurses in tumour specialized hospitals, in order to provide a theoretical basis for managers to manage and train nurses, improve their safety behaviour level and ensure medical safety.DesignAn anonymous cross‐sectional survey.MethodA total of 2147 nurses from Grade A cancer hospitals in 15 provinces of China were selected by a convenient sampling method. Questionnaires were collected through the Questionnaire Star pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that self-efficacy can predict a reduction in burnout, especially in specific domains that affect the pressure of working conditions, such as communication skills. These findings underscore the importance of self-efficacy in maintaining a high work-related quality of life, which is critical to both the well-being of the workforce and the efficacy of the health care system [34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that self-efficacy can predict a reduction in burnout, especially in specific domains that affect the pressure of working conditions, such as communication skills. These findings underscore the importance of self-efficacy in maintaining a high work-related quality of life, which is critical to both the well-being of the workforce and the efficacy of the health care system [34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%